TINJAUAN YURIDIS KEABSAHAN MATA UANG CRYPTO (CRYPTOCURRENCY) BERDASARKAN PERSPEKTIF UNDANG-UNDANG NOMOR 7 TAHUN 2011 TENTANG MATA UANG - Cucumandalin, I Ketut Samuel; ardhya, si ngurah; Adnyani, Ni Ketut Sari; Kusuma, Putu Riski Ananda (Universitas Pendidikan Ganesha, 2024)
This study aims (1) to analyze legal arrangements regarding cryptocurrencies as a reference in providing legal certainty for the use of cryptocurrency in Indonesia, (2) identify the validity of cryptocurrencies based on the perspective of Law Number 7 of 2011 concerning Currency.The type of Penlitain used by researchers is normative legal research, namely through a statutory approach, and a conceptual approach. The sources of legal materials used are the 1945 Constitution, Civil Code, PERPRES, Permendagri, Bappebti, and PBI. The results showed that (1) Juridically normatively, Indonesian law already has provisions or regulations regarding